(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2019)
Surface materials that turn into hard surface material and lack of vegetations are some of the effects of rapid development that can affect the micro climate in urban areas. This happened on Cik Ditiro corridor in the city of Yogyakarta which had quite dense activities, this was marked by various functions of land use and human activities throughout the day. The method is simulation method that uses the EnviMET 4.0 software and the empirical measurements. This method is to simulate the value of each climate variable in existing conditions and ideal conditions. The results of this research show that the condition of the Cik Ditiro corridor still belongs to the heat which is uncomfortable thermal conditions. Recommendations result of this research is to make better thermal comfort on corridor. The result of this research to give recommendations in terms of improving better for thermal comfort.